Rapid preparation method of composite thermal runaway protection material

The composite thermal runaway protection materials are rapidly prepared through the primary mixing process and the secondary homogenization process, which solves the problems of low production efficiency and low packaging efficiency in the existing technology, and achieves efficient and dense thermal runaway protection, avoiding the fire of the battery pack. and explosion.

CN119390390APending Publication Date: 2025-02-07YANGTZE OPTICAL CHEMISTRY CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411395861.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-16
Filing Date
2024-10-08
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing thermal runaway protective materials have low production efficiency and low packaging efficiency, which is difficult to ensure compactness, and are not suitable for large-scale production, so it is impossible to effectively achieve rapid molding and mass production of thermal runaway protective materials.

Method used

Using primary mixing process and secondary homogenization process, the composite thermal runaway protection materials can be quickly prepared through the molding and curing process of uniform mixtures, including inorganic heat-absorbing materials, inorganic light-guiding materials, polyvinyl alcohol, and long-chain alkyl diacids. and UV curing packaging resin, with high heat absorption enthalpy and porous structure, effectively insulating heat to prevent heat transfer.

Benefits of technology

The rapid molding and mass production of composite thermal runaway protective materials is realized, the strength and compactness of the materials are improved, effective protection against thermal runaway of the battery is ensured, and fire and explosion of the battery pack are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390390A_ABST
    Figure CN119390390A_ABST
Patent Text Reader

Abstract

The invention discloses a rapid preparation method of a composite thermal runaway protection material. The composite thermal runaway protection material comprises the following components in percentage by mass: 71-95% of an inorganic heat absorption material, 0-5% of an inorganic light guide material, 0-12% of polyvinyl alcohol, 0-1% of long-chain alkyl diacid and 5-16% of UV curing packaging resin. The preparation method comprises the following steps: obtaining a fluffy mixture by using a mixing process, homogenizing the fluffy mixture through secondary homogenizing equipment by using a homogenizing process, controlling the temperature of the mixture in the homogenizing process to be 0-80 DEG C, and performing a forming process and a curing process on the uniform mixture to obtain the composite thermal runaway protection material. A homogenizing process is added, so that the powder spreading uniformity in the process of preparing the large-area large-size composite thermal runaway protection material is improved, and the strength of the composite thermal runaway protection material is improved. The heat absorption enthalpy value of the composite thermal runaway protection material is high, so that the adjacent batteries are prevented from continuously heating, and fire explosion is avoided; and the surface of the inorganic heat-absorbing material is coated with UV-cured packaging resin, so that stable packaging of the inorganic heat-absorbing material is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermal runaway protection materials, and in particular relates to a method for rapidly preparing a composite thermal runaway protection material. Background Art

[0002] High energy density batteries, especially lithium-ion batteries, have been widely used in electric vehicles, portable electronic devices and energy storage systems. However, with the increase in battery capacity and energy density, its safety issues have become increasingly prominent, especially the problem of thermal runaway. Thermal runaway refers to the rapid rise in temperature of the battery due to the runaway of internal chemical reactions under certain conditions, which may cause safety accidents such as fire or explosion. The main triggering factors are; internal short circuit: internal short circuit caused by mechanical abuse, electrical abuse and other reasons is a common triggering factor of thermal runaway. Overcharging: Overcharging will cause the internal pressure of the battery to increase, the electrolyte to decompose, and generate a lot of heat. High temperature environment: Batteries that work in high temperature environment for a long time are more likely to have thermal runaway. As the cost of raw materials for lithium-ion batteries continues to rise, sodium-ion batteries have become a research hotspot as a new generation of power batteries with lower theoretical cost, but sodium-ion batteries also have the problem of thermal runaway. This makes the improvement of lithium / sodium battery safety one of the important topics in the field of battery research.

[0003] Existing thermal management solutions mainly use aerogel or insulation panels to separate each battery pack component. After a single battery pack thermal runaway, the heat can be isolated within a limited range under non-serious conditions. However, aerogel cannot slow down the progress of thermal runaway. Once thermal runaway occurs, there is still a possibility of spillover to adjacent battery packs, resulting in continued thermal runaway and fire or explosion.

[0004] Chinese patent CN202310479415.0 records a fast-absorbing thermal runaway protection material and its preparation method, which successfully applies chemical inorganic heat-absorbing materials to the thermal runaway diffusion of batteries. The preparation and molding process in the patent is room temperature curing for 24 hours, which has certain bottlenecks for the mass production of thermal runaway protection materials with rapid development needs. It is mainly manifested in low production efficiency and low packaging efficiency. During the production process, the thermal runaway protection material is filled into the shell, and it is difficult to ensure the density. In addition, the filling efficiency is extremely low, which is not suitable for large-scale production on the production line. How to effectively realize the rapid prototyping of thermal runaway protection materials and reduce manufacturing costs has become an urgent problem to be solved in the industrialization of thermal runaway protection materials. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a rapid preparation method of a composite thermal runaway protection material. A secondary homogenization process is added on the basis of a primary mixing process in the preparation process to realize the rapid prototyping of the composite thermal runaway protection material. The composite thermal runaway protection material can be used for lithium-ion batteries and sodium-ion batteries, and can be designed according to different battery structures, so as to be placed between battery packs, or to place one piece every a certain number of battery packs. The composite thermal runaway protection material of the present invention has a high endothermic enthalpy value (the endothermic enthalpy of inorganic endothermic materials>1300J / g), and a chemical reaction will occur between 90 and 400°C and actively absorb heat. Usually, the battery pack will heat up rapidly after thermal runaway, so that the composite thermal runaway protection material reaches above 90°C. At this time, the material will spontaneously endothermically decompose. Because the material has a high enthalpy value, a continuous endothermic effect is formed, which drives the temperature of the runaway battery pack to drop. Even after the material is decomposed, the protective material will form a porous structure, becoming an excellent thermal insulation material, preventing heat from being transferred to adjacent batteries, preventing adjacent batteries from continuing to heat up, and avoiding fire and explosion.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme: a rapid preparation method of a composite thermal runaway protection material, the composite thermal runaway protection material includes the following components by mass percentage: 71-95% of inorganic heat absorbing material, 0-5% of inorganic light guiding material, 0-12% of polyvinyl alcohol, 0-1% of long-chain alkyl diacid and 5-16% of UV curing encapsulation resin;

[0007] The rapid preparation method of the composite thermal runaway protection material is as follows:

[0008] S1, using a mixing process to obtain a fluffy mixture;

[0009] S2, through a homogenization process, the fluffy mixture is homogenized by a secondary homogenization device, the temperature of the mixture during the homogenization process is 0 to 80° C., and a uniform mixture is obtained;

[0010] S3. Performing a molding process and a curing process on the uniform mixture to obtain a composite thermal runaway protection material.

[0011] In the above technical solution, in step S1, the mixing process adds the inorganic heat absorbing material, the inorganic light guiding material, the polyvinyl alcohol, the long-chain alkyl diacid and the UV curing encapsulation resin into a mixing device, stirs while adding, the temperature range of the mixture in the mixing process is 0 to 80° C., the mixing time is greater than 10 minutes, and the air bubbles are removed by vacuum to obtain a fluffy mixture;

[0012] The fluffy mixture has a specific gravity of less than 1g / cm 3 ;

[0013] In the step S3, the molding process adds the uniform mixture into a mold and uses a press to press to obtain a molding material, the molding temperature is 0 to 80° C., and the molding pressure is greater than 3 MPa;

[0014] In step S3, the curing process takes out the molding material and uses a UV lamp to cure it on one side or both sides. The curing starting material temperature is 0 to 60° C., and the highest temperature of the material after curing does not exceed 80° C.

[0015] In the above technical solution, the method also includes a grinding process. In order to facilitate installation, the material after the curing process in step S3 is ground by a CNC machine tool to obtain a composite thermal runaway protection material with a smooth surface. The material temperature does not exceed 80°C during the grinding process.

[0016] In the above technical solution, in step S2, the secondary homogenization equipment includes any one of a three-roll mill, a calender, a sand mill, a roller press or a colloid mill.

[0017] Preferably, the primary mixing equipment includes any one of a reaction kettle, a dispersion kettle, a mixing kettle, a kneader, a planetary mixer or a gear pump with a buffer tank.

[0018] Preferably, the press comprises a four-column hydraulic press, a frame hydraulic press, an electric screw press or a precision servo press, preferably a press whose hydraulic speed and pressure lifting speed can be controlled by a computer.

[0019] Preferably, the mold is made of metal with Teflon coating on the surface, or an isolation film is placed on the upper and lower surfaces of the mold. Preferably, the isolation film includes PET release film, PP film, PTFE film, PE film, ETFE film or release paper. The mold is designed according to the model required by the customer to achieve high-density and rapid shaping.

[0020] Preferably, the ultraviolet lamp is a high-pressure mercury lamp or a metal halide lamp, and preferably the ultraviolet lamp is a composite ultraviolet lamp composed of one or more ultraviolet lamps in the 365nm band, the 385nm band, the 395nm band, and the 405nm band; the installation form of the ultraviolet lamp includes single-sided installation, top and bottom aligned installation, or top and bottom staggered installation, and the irradiation power received by the material surface is greater than 30mW / cm 2 , irradiation dose greater than 1J / cm 2 ; In the curing process, the curing depth can reach 40mm for double curing of the surface and bottom layers.

[0021] Preferably, the pressure applied by the press to the material is greater than 3 MPa, and the molding temperature is 0-80° C., preferably the mold is heated or the pressure plate of the press is heated.

[0022] In the above technical scheme, the inorganic heat absorbing material includes sodium acetate trihydrate, ammonium iron oxalate trihydrate, magnesium sulfate heptahydrate, zinc sulfate heptahydrate, sodium carbonate decahydrate, calcium chloride hexahydrate, magnesium chloride hexahydrate, aluminum nitrate nonahydrate, ammonium pentaborate octahydrate, ammonium ferric sulfate dodecahydrate, ferrous chloride tetrahydrate, ammonium oxalate monohydrate, sodium tetraborate decahydrate, sodium tetraborate pentahydrate, aluminum sulfate 18hydrate, ammonium pentaborate, ammonium hydrogen borate tetrahydrate, boric acid, barium hydroxide octahydrate, sodium silicate pentahydrate, hydrated sodium aluminosilicate, silicic acid, and sodium hydroxide. , hydrated silicic acid, potassium aluminum sulfate dodecahydrate, sodium sulfate decahydrate, copper sulfate heptahydrate, ferrous sulfate heptahydrate, cobalt chloride hexahydrate, calcium sulfate dihydrate, etc., a mixture in any proportion; preferably, the inorganic endothermic material includes a mixture in any proportion of one or more of ammonium oxalate monohydrate, sodium acetate trihydrate, boric acid, ammonium pentaborate octahydrate, barium hydroxide octahydrate, sodium tetraborate decahydrate, potassium aluminum sulfate dodecahydrate, sodium sulfate decahydrate or calcium sulfate dihydrate, preferably with a mesh size of 80 to 300 meshes.

[0023] In the above technical scheme, the inorganic light-conducting material is a material with transmittance to ultraviolet light, including a mixture of any one or more of spherical silicon powder, granular silicon powder, glass powder, quartz chopped fibers or glass chopped fibers in any proportion; preferably, the fiber diameter is 3 to 300 μm, the length is 0.5 to 5 mm, and the average particle size of the powder is preferably 80 to 300 mesh; the inorganic light-conducting material can enhance the overall strength of the thermal protection material, improve the high temperature resistance, and can also transmit the ultraviolet light on the surface to the deep layer, thereby realizing dual curing of the surface and the deep layer.

[0024] In the above technical solution, the long-chain alkyl diacid includes a mixture of any one or more of dodecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid or eicosanedioic acid in any proportion;

[0025] The polyvinyl alcohol is a powder, preferably with a mesh size of 80 to 300 meshes. The polyvinyl alcohol structure contains a large number of hydroxyl groups and has good water absorption. A small amount of water can be adsorbed on the surface of the powder. The water can undergo a hydrolysis reaction with the siloxane structure in the UV encapsulation resin to form a silanol structure, and then undergo a condensation reaction with the hydroxyl group or crystal water on the surface of the inorganic heat-absorbing material, thereby enhancing the interface bonding force between the encapsulation resin and the inorganic heat-absorbing material.

[0026] In the above technical solution, the composite thermal runaway protection material is cut into suitable sizes according to the structure of the battery pack and packaged in a sealed and pressure-resistant shell. Depending on the application scenario of the energy storage battery, it can be packaged with independent thermal runaway protection materials or packaged after being attached with thermal insulation buffer materials to increase the compression ratio of the thermal protection material and buffer the expansion and extrusion of the battery.

[0027] In the above technical solution, the composite thermal runaway protection material is used alone as a thermal runaway protection material, or is used in combination with a thermal insulation material or a physical thermal insulation structure to form a thermal protection system. The composite thermal runaway protection material is used as a heat absorbing material in the thermal protection system.

[0028] In the above technical solution, the UV curing encapsulation resin comprises, by mass percentage: 25-70% of siloxane-epoxy resin composite modified polyurethane acrylate, 10-30% of siloxane-polyurethane composite modified epoxy acrylate, 0-5% of epoxy resin, 5-40% of epoxy acrylate, 0-1% of acrylic acid, 5-30% of active monomer, 0-20% of silane modified resin, 0.1-3% of dehydrating agent, 0.1-3% of photoinitiator and 0.01-0.3% of polymerization inhibitor;

[0029] The preparation method of UV curing encapsulation resin is as follows: add the siloxane-epoxy resin composite modified polyurethane acrylate, siloxane-polyurethane composite modified epoxy acrylate, epoxy resin, epoxy acrylate, acrylic acid, active monomer, silane modified resin, photoinitiator and inhibitor in the above components into a reactor according to a proportion, maintain stirring at 50-60° C. for 2-3 hours, add a dehydrating agent, stir for 10-30 minutes, and obtain a UV curing encapsulation resin.

[0030] In the above technical solution, the epoxy resin refers to a substance containing epoxy bonds in the molecular structure, including a mixture of any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol E epoxy resin, bisphenol S epoxy resin, epoxy soybean oil, cardanol modified epoxy resin, trimethylolpropane triglycidyl ether, hexanediol diglycidyl ether or phenyl glycidyl ether in any proportion;

[0031] The epoxy acrylate is a product obtained by mixing acrylic acid and carboxyethyl acrylate in any proportion and ring-opening the mixture with the above epoxy resin, including CN104 NS or CN120NS of Sartomer;

[0032] The active monomer is an acrylate monomer with 1-6 functions and does not contain a hydroxyl structure, including a mixture of any one or more of isobornyl acrylate, 2-cyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, 1,6-hexanediol diacrylate, isobornyl methacrylate or tetrahydrofurfuryl methacrylate in any proportion;

[0033] The silane-modified resin is a resin terminated with an alkoxysilyl group, including any one or more of a silane-modified polyether resin, a silane-modified polyacrylate resin, a silane-modified polyurethane resin, a silane-modified polyester resin or an alkoxy silicone resin, in any proportion; preferably, the alkoxysilane group includes trimethoxysilane, triethoxysilane, methyldimethoxysilane or methyldiethoxysilane;

[0034] The dehydrating agent is toluenesulfonyl isocyanate, which can effectively remove residual moisture in the system, prevent the hydrolysis of siloxane on the siloxane-epoxy resin composite modified polyurethane acrylate structure, and improve the storage stability of UV curing encapsulation resin;

[0035] The photoinitiator is a substance that can decompose or abstract hydrogen to generate free radicals under ultraviolet light irradiation, including any one or more of 4-benzoyl-4'-methyl-diphenyl sulfide (BMS), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), 2,4,6-trimethylbenzoylphosphonic acid ethyl ester (TPO-L), bis(2,4,6-trimethylbenzyl acyl)phenylphosphine oxide (819), benzoin dimethyl ether (651), 2-methyl-1-(4-methylmercaptophenyl)-2-morpholine-1-propanone (907), 1-hydroxycyclohexyl benzophenone (184), 4-acryloyloxybenzophenone or methyl o-benzoylbenzoate (OMBB) in any proportion. Under ultraviolet light irradiation, the surface of the material will be quickly solidified and formed to form a material with a certain strength, which is conducive to subsequent transportation.

[0036] In the above technical scheme, the preparation method of the siloxane-epoxy resin composite modified polyurethane acrylate is as follows:

[0037] A1, adding diisocyanate and hydroxy acrylate in a molar ratio of 1:1 into reactor A, adding 0.01-0.2% of the total mass of diisocyanate and hydroxy acrylate as catalyst dibutyltin dilaurate, and 0.01-0.2% of the total mass of diisocyanate and hydroxy acrylate as inhibitor p-hydroxyanisole, raising the temperature to 40-60° C. for reaction for 1-3 hours to obtain a semi-adduct of diisocyanate and hydroxyethyl acrylate, and calculating the theoretical NCO equivalent;

[0038] A2, adding epoxy resin and mercaptosilane coupling agent into reactor B in a molar ratio of epoxy bond to mercapto group of 1:1, adding catalyst triethylamine in an amount of 0.01-0.2% of the total mass of epoxy resin and mercaptosilane coupling agent, heating to 70-90° C. for reaction for 1-3 hours to obtain siloxane-modified epoxy resin, and calculating the theoretical hydroxyl equivalent;

[0039] A3. According to the calculation method of NCO equivalent: hydroxyl equivalent = semi-adduct mass: siloxane-modified epoxy resin mass, a set amount of siloxane-modified epoxy resin is added into reactor A, 0.01-0.2% of the total mass of the siloxane-modified epoxy resin is added as catalyst dibutyltin dilaurate, and 0.01-0.2% of the total mass of the siloxane-modified epoxy resin is added as inhibitor p-hydroxyanisole, the reaction is maintained at 60-80° C. with stirring for 2-8 hours, and an infrared spectrometer is used to detect the wavelength at 2260 cm -1 After the isocyanate absorption peaks of about 100 Å disappear, the siloxane-epoxy resin composite modified polyurethane acrylate is obtained.

[0040] Furthermore, in step A1, 0 to 30% of the total mass of diisocyanate and hydroxy acrylate and 1 to 6 functional acrylate monomers without hydroxyl structure are added; in step A2, 0 to 30% of the total mass of epoxy resin and mercaptosilane coupling agent and 1 to 6 functional acrylate monomers without hydroxyl structure are added;

[0041] Or in step A1, 0 to 30% of the total mass of diisocyanate and hydroxy acrylate in an amount of 1 to 6 functional acrylate monomers without hydroxyl structure is added; in step A3, 0 to 30% of the total mass of siloxane-modified epoxy resin in an amount of 1 to 6 functional acrylate monomers without hydroxyl structure is added;

[0042] Or in step A2, 0 to 30% of the total mass of epoxy resin and mercaptosilane coupling agent is added with 1-6 functional acrylate monomers without hydroxyl structure; in step A3, 0 to 30% of the total mass of siloxane-modified epoxy resin is added with 1-6 functional acrylate monomers without hydroxyl structure;

[0043] Or in step A1, 0 to 30% of the total mass of diisocyanate and hydroxy acrylate and 1 to 6 functional acrylate monomers without hydroxyl structure are added; in step A2, 0 to 30% of the total mass of epoxy resin and mercaptosilane coupling agent and 1 to 6 functional acrylate monomers without hydroxyl structure are added; in step A3, 0 to 30% of the total mass of siloxane-modified epoxy resin and 1 to 6 functional acrylate monomers without hydroxyl structure are added.

[0044] Furthermore, in step A1, 0 to 30% of the total mass of diisocyanate and hydroxy acrylate and a 1-6 functional acrylate monomer without a hydroxyl structure is added;

[0045] Or in step A2, 0 to 30% of the total mass of the epoxy resin and the mercaptosilane coupling agent is added with a 1-6 functional acrylate monomer that does not contain a hydroxyl structure;

[0046] Or in step A3, 0 to 30% of the total mass of the silicone-modified epoxy resin is added with 1-6 functional acrylate monomers that do not contain hydroxyl structures.

[0047] Specifically, the acrylate monomer includes a mixture of any one or more of isobornyl acrylate, 2-cyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, 1,6-hexanediol diacrylate, isobornyl methacrylate or tetrahydrofurfuryl methacrylate in any proportion.

[0048] Specifically, in step A1, the diisocyanate includes any one or more of hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), toluene diisocyanate (including T100 / T80 / T65), xylylene diisocyanate (XDI), trimethyl diisocyanate (TMDI), 1,5-naphthalene diisocyanate (NDI) or diphenylmethane diisocyanate (MDI-100 / MDI-50) in any proportion;

[0049] In step A1, the hydroxy acrylate includes a mixture of any one or more of 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-hydroxypropyl acrylate, 2-hydroxybutyl acrylate or 4-hydroxybutyl acrylate in any proportion;

[0050] In step A2, the epoxy resin refers to a substance containing epoxy bonds in its molecular structure, including a mixture of any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol E epoxy resin, bisphenol S epoxy resin, epoxy soybean oil, cardanol-modified epoxy resin, trimethylolpropane triglycidyl ether, hexanediol diglycidyl ether or phenyl glycidyl ether in any proportion;

[0051] In step A2, the mercaptosilane coupling agent includes a mixture of any one or more of mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane, mercaptopropylmethyldimethoxysilane or mercaptopropylmethyldiethoxysilane in any proportion.

[0052] In the above technical scheme, the preparation method of the siloxane-polyurethane composite modified epoxy acrylate is as follows:

[0053] B1, adding diisocyanate and mercaptosilane coupling agent in a molar ratio of 1:1 into reactor C, adding 0.01-0.2% of the total mass of diisocyanate and mercaptosilane coupling agent as catalyst dibutyltin dilaurate, heating to 70-100° C. and reacting for 4-8 hours to obtain a semi-adduct of diisocyanate and mercaptosilane coupling agent;

[0054] B2. Add a set mass of epoxy acrylate to the reactor C at a molar ratio of diisocyanate to epoxy acrylate of 1:1 to 1:0.5, add a catalyst dibutyltin dilaurate of 0.01 to 0.2% of the total mass of epoxy acrylate, maintain the temperature at 70 to 90° C. for 1 to 3 hours to obtain siloxane-polyurethane composite modified epoxy acrylate.

[0055] Furthermore, in step B1, 0 to 30% of the total mass of diisocyanate and mercaptosilane coupling agent is added with 1-6 functional acrylate monomers that do not contain hydroxyl structure; in step B2, 0 to 30% of the total mass of epoxy acrylate is added with 1-6 functional acrylate monomers that do not contain hydroxyl structure.

[0056] Furthermore, in step B1, 0 to 30% of the total mass of diisocyanate and mercaptosilane coupling agent is added with 1-6 functional acrylate monomers that do not contain hydroxyl structures;

[0057] Or in step B2, 0 to 30% of the total mass of epoxy acrylate is added with 1-6 functional acrylate monomers that do not contain hydroxyl structures.

[0058] Specifically, the acrylate monomer includes a mixture of any one or more of isobornyl acrylate, 2-cyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, 1,6-hexanediol diacrylate, isobornyl methacrylate or tetrahydrofurfuryl methacrylate in any proportion.

[0059] Specifically, in step B1 or B2, the diisocyanate includes any one or more of hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), toluene diisocyanate (including T100 / T80 / T65), xylylene diisocyanate (XDI), trimethyl diisocyanate (TMDI), 1,5-naphthalene diisocyanate (NDI) or diphenylmethane diisocyanate (MDI-100 / MDI-50) in any proportion;

[0060] In step B1, the mercaptosilane coupling agent includes a mixture of any one or more of mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane, mercaptopropylmethyldimethoxysilane or mercaptopropylmethyldiethoxysilane in any proportion.

[0061] Compared with the prior art, the present invention has the following beneficial effects:

[0062] 1. The composite thermal runaway protection material molding process described in the present invention adds a secondary homogenization process on the basis of a primary mixing process, thereby improving the uniformity of the encapsulation resin and the powder, improving the uniformity of the powder spreading in the process of preparing large-area and large-size composite thermal runaway protection materials, and improving the strength of the composite thermal runaway protection materials.

[0063] 2. The composite thermal runaway protection material described in the present invention is an organic-inorganic composite material. A UV-curing encapsulation resin is coated on the surface of the inorganic heat-absorbing material to achieve stable encapsulation of the inorganic heat-absorbing material. Moreover, after being irradiated with ultraviolet light, the inorganic light-guiding material can guide the ultraviolet light into the deep layer to achieve dual curing of the surface and deep layer, thereby meeting the one-time curing and molding requirements for the 40mm thick composite thermal runaway protection material.

[0064] 3. The composite thermal runaway protection material of the present invention has a high endothermic enthalpy value, and after the inorganic endothermic material is decomposed, the protection material will form a porous structure, becoming an excellent thermal insulation material, preventing heat from being transferred to adjacent batteries, preventing adjacent batteries from continuing to heat up, and avoiding fire and explosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:

[0066] Figure 1 This is a schematic diagram of a rapid preparation process of a composite thermal runaway protection material according to the present invention;

[0067] Figure 2 It is a schematic diagram of the curing process of the composite thermal runaway protection material of the present invention;

[0068] In the figure: inorganic heat absorbing material 1; inorganic light guiding material 2; polyvinyl alcohol 3; inorganic light guiding material light transmission 4; UV curing encapsulating glue (before curing) 5; UV curing encapsulating glue (after curing) 6;

[0069] Figure 3 This is a schematic diagram of the endothermic decomposition process of the composite thermal runaway protection material of the present invention;

[0070] In the figure: inorganic heat absorbing material 1; inorganic heat absorbing material decomposition residue 2; polyvinyl alcohol 3; UV curing encapsulation glue (after curing) 4; inorganic light guiding material 5; pores formed after decomposition of inorganic heat absorbing material 6;

[0071] Figure 4 It is a schematic diagram of the test device of the present invention. DETAILED DESCRIPTION

[0072] In order to better understand the present invention, the present invention is further described below through specific implementation modes, but it is not intended to limit the present invention.

[0073] Figure 1This is a flow chart of the rapid preparation process of the composite thermal runaway protection material of the present invention. Inorganic heat absorbing material, inorganic light guiding material, polyvinyl alcohol, long-chain alkyl diacid and UV curing encapsulation resin are mixed, homogenized, formed, cured and polished by mass percentage to obtain the composite thermal runaway protection material. A homogenization process is added on the basis of the mixing process in the preparation process to achieve rapid prototyping of the composite thermal runaway protection material.

[0074] Figure 2 This is the curing process of the composite thermal runaway protection material of the present invention. The surface of the composite thermal runaway protection material is coated with a UV curing encapsulation resin. After being irradiated with ultraviolet light, the inorganic light-guiding material inside the adhesive resin guides the ultraviolet light into a deep layer to achieve one-time curing and molding.

[0075] Figure 3 This is the endothermic decomposition diagram of the composite thermal runaway protection material of the present invention. The endothermic enthalpy of the composite thermal runaway protection material is high (the endothermic enthalpy of inorganic endothermic material>1200J / g). The battery pack quickly heats up after thermal runaway, so that the composite thermal runaway protection material reaches above 90°C. At this time, the material will spontaneously endothermically decompose, forming a continuous endothermic effect, driving the temperature of the runaway battery pack to drop. After the decomposition of the protection material is completed, a porous structure will be formed on the surface of the material, becoming an excellent thermal insulation material to prevent heat transfer and avoid fire and explosion of the battery pack.

[0076] Some of the special raw materials used in the following examples are shown in Table 1.

[0077] Table 1

[0078]

[0079]

[0080]

[0081] The specific preparation methods of the siloxane-epoxy resin composite modified polyurethane acrylate and the siloxane-polyurethane composite modified epoxy acrylate used in the present invention are as follows:

[0082] 1. Preparation of siloxane-epoxy resin composite modified polyurethane acrylate:

[0083] A1: 444.58 g (2 mol) of isophorone diisocyanate, 236.98 g (2 mol, purity 98%) of 2-hydroxyethyl acrylate, 0.4 g of catalyst (dibutyltin dilaurate) and 0.5 g of inhibitor (p-hydroxyanisole) were added to reactor A, and the temperature was raised to 40-45° C. for reaction for 3 hours to obtain a semi-adduct of diisocyanate and hydroxyethyl acrylate, and the calculated theoretical NCO equivalent was 341.23 g / mol;

[0084] A2: Add 510 g (1.5 mol of epoxy resin, 3 mol of epoxy bond) of bisphenol F epoxy resin, 841.11 g (3 mol) of mercaptopropyl triethoxysilane and 1.35 g of catalyst (triethylamine) into another reactor B, heat to 85° C. and react for 2.5 hours to obtain a siloxane-modified epoxy resin for standby use, with a calculated theoretical hydroxyl equivalent of 450.82 g / mol;

[0085] A3: According to the calculation method of NCO equivalent: hydroxyl equivalent = semi-adduct mass: siloxane-modified epoxy resin mass, there are 682.46g of semi-adduct in reactor A. Add 901.64g of siloxane-modified epoxy resin into reactor A, add 180g of 1,6-hexanediol diacrylate, add 0.7g of catalyst (dibutyltin dilaurate) and 0.9g of inhibitor (p-hydroxyanisole), maintain 70-75℃ stirring reaction for 4 hours, and use infrared spectrometer to detect 2260cm -1 After the isocyanate absorption peaks of about 1:1 disappear, the siloxane-epoxy resin composite modified polyurethane acrylate Si / EP-PUA1 is obtained.

[0086] 2. Preparation of siloxane-polyurethane composite modified epoxy acrylate:

[0087] B1: 222.29 g (1 mol) of isophorone diisocyanate, 280.37 g (1 mol) of mercaptopropyl triethoxysilane and 0.4 g of a catalyst (dibutyltin dilaurate) were added to a reactor C, and the temperature was raised to 70-80° C. for reaction for 5-6 hours to obtain a semi-adduct of diisocyanate and mercaptosilane coupling agent;

[0088] B2: Add 350 g of epoxy acrylate (CN104NS) and 0.3 g of catalyst (dibutyltin dilaurate) in a molar ratio of diisocyanate to epoxy acrylate of 1:0.7 into reactor C, maintain the temperature at 80-90°C for 2-2.5 hours to obtain the siloxane-polyurethane composite modified epoxy acrylate Si / PUA-EP1.

[0089] Embodiment 1:

[0090] A rapid preparation method of a composite thermal runaway protection material, wherein the composite thermal runaway protection material comprises, by mass percentage, 40% hydrated silicate, 45% magnesium chloride hexahydrate, 5% polyvinyl alcohol, 0.3% hexadecanedioic acid, and 9.7% UV curing encapsulation resin UV-3. The preparation method is as follows:

[0091] S1 mixing process: 400g of hydrated silicate, 450g of magnesium chloride hexahydrate, 50g of polyvinyl alcohol, 3g of hexadecanedioic acid, and 97g of UV curing encapsulation resin UV-3 are added into a primary mixing kettle, and stirred while adding. The temperature range of the mixture during the mixing process is 20-30°C, and the mixing time is 15 minutes. Vacuum the mixture to remove bubbles and obtain a fluffy mixture;

[0092] S2 homogenization process: The mixture obtained by the primary mixing equipment is homogenized by a three-roller mill. The temperature of the mixture during the homogenization process ranges from 20 to 30°C to obtain a uniform mixture;

[0093] S3 molding process: add the uniform mixture into a 227mm×160mm×2mm mold with a polytetrafluoro coating on the surface, and use the mold to press and mold under a hydraulic press. The feed weight is 116.3g, the molding temperature is 35±5℃, and the molding pressure is 8.7MPa;

[0094] S3 curing process: Take out the pressed material and place it under 100mW / cm 2 Irradiation under metal halide lamp for 40 seconds, the irradiation dose is 4J / cm 2 ; The starting temperature of the curing material is 30-35°C, and the maximum temperature of the material after curing is 60°C;

[0095] S3 grinding process: In order to facilitate installation, the cured material can be grinded by CNC (numerical control machine) to obtain a composite thermal runaway protection material R-2 with a smooth surface. The maximum temperature of the material during the grinding process is 45°C.

[0096] The UV curable encapsulation resin UV-3 comprises the following components by mass percentage: 44.4% of siloxane-epoxy resin composite modified polyurethane acrylate Si / EP-PUA1, 25% of siloxane-polyurethane composite modified epoxy acrylate Si / PUA-EP1, 1% of bisphenol A epoxy resin, 15% of epoxy acrylate, 1% of acrylic acid, 10% of active monomer (dipropylene glycol diacrylate), 0.5% of p-toluenesulfonyl isocyanate, 1% of photoinitiator (184), 1% of 4-acryloxybenzophenone, 1% of photoinitiator (TPO), and 0.1% of inhibitor (p-hydroxyanisole);

[0097] The preparation method is as follows: 444g of siloxane-epoxy resin composite modified polyurethane acrylate Si / EP-PUA1, 250g of siloxane-polyurethane composite modified epoxy acrylate Si / PUA-EP1, 10g of bisphenol A epoxy resin, 150g of epoxy acrylate (CN120 NS), 10g of acrylic acid, 100g of active monomer (dipropylene glycol diacrylate), 10g of photoinitiator (184), 10g of 4-acryloxybenzophenone, 10g of photoinitiator (TPO), and 1g of inhibitor (p-hydroxyanisole) are added into a reactor, stirred at 55°C for 2.5 hours, 5g of p-toluenesulfonyl isocyanate is added, and stirred for 20 minutes to obtain a UV-curable encapsulation resin UV-3.

[0098] The thermal conductivity, material enthalpy, density, average thickness and compressive strength of the composite thermal runaway protection material R-2 prepared in this embodiment are measured and are shown in Table 2.

[0099] Embodiment 2:

[0100] A rapid preparation method of a composite thermal runaway protection material, wherein the composite thermal runaway protection material comprises, by mass percentage, 88% of potassium aluminum sulfate dodecahydrate, 2% of quartz chopped fiber, 2% of polyvinyl alcohol, 0.3% of hexadecanedioic acid, and 7.7% of UV-curable encapsulation resin UV-4. The preparation method is as follows:

[0101] S1 mixing process: 880g of potassium aluminum sulfate dodecahydrate, 20g of quartz chopped fiber, 20g of polyvinyl alcohol, 3g of hexadecanedioic acid, and 77g of UV curing encapsulation resin UV-4 are added into a primary mixing kettle, and stirred while adding. The temperature range of the mixture during the mixing process is 30-35°C, and the mixing time is 25 minutes. Vacuum and remove bubbles to obtain a fluffy mixture;

[0102] S2 homogenization process: The mixture obtained by the primary mixing equipment is homogenized by a calender. The temperature range of the mixture during the homogenization process is 40-45°C to obtain a uniform mixture;

[0103] S3 molding process: add the uniform mixture into a 227mm×160mm×10mm mold with a polytetrafluoro coating on the surface, and use the mold to press and mold under a hydraulic press. The feed weight is 581.5g, the molding temperature is 40±5℃, and the molding pressure is 10MPa;

[0104] S3 curing process: Take out the pressed material and place it under 100mW / cm 2 Irradiation under metal halide lamp for 60 seconds, the irradiation dose is 6J / cm 2 ; The starting material temperature of the curing is 30-35°C, and the highest temperature of the material after curing is 68°C;

[0105] S3 grinding process: In order to facilitate installation, the cured material can be grinded by CNC (numerical control machine) to obtain a composite thermal runaway protection material R-10 with a smooth surface. The maximum temperature of the material during the grinding process is 40°C.

[0106] The UV curable encapsulation resin UV-4 comprises the following components by mass percentage: 41.6% of siloxane-epoxy resin composite modified polyurethane acrylate Si / EP-PUA1, 15% of siloxane-polyurethane composite modified epoxy acrylate Si / PUA-EP1, 18.3% of epoxy acrylate, 9% of active monomer (trimethylolpropane triacrylate), 12% of active monomer (tripropylene glycol diacrylate), 1% of p-toluenesulfonyl isocyanate, 0.5% of photoinitiator (184), 1% of 4-acryloxybenzophenone, 1.5% of photoinitiator (TPO), and 0.1% of inhibitor (p-hydroxyanisole); the preparation method thereof is the same as that of the UV curable encapsulation resin UV-3 in Example 1.

[0107] The thermal conductivity, material enthalpy, density, average thickness and compressive strength of the composite thermal runaway protection material R-10 prepared in this embodiment are measured and are shown in Table 2.

[0108] Embodiment 3:

[0109] A rapid preparation method of a composite thermal runaway protection material, wherein the composite thermal runaway protection material comprises, by mass percentage: 40% potassium aluminum sulfate dodecahydrate, 46.4% magnesium chloride hexahydrate, 1% quartz chopped fiber, 1% silicon powder, 1% polyvinyl alcohol, 0.6% eicosanedioic acid, and 10% UV curing encapsulation resin UV-4. The preparation method is as follows:

[0110] S1 mixing process: 800g of potassium aluminum sulfate dodecahydrate, 928g of magnesium chloride hexahydrate, 20g of quartz chopped fiber, 20g of silicon powder, 20g of polyvinyl alcohol, 12g of eicosanedioic acid, and 200g of UV curing encapsulation resin UV-4 are added into a primary mixing kettle, and stirred while adding. The temperature range of the mixture during the mixing process is 30-35°C, and the mixing time is 25 minutes. Vacuum the mixture to remove bubbles and obtain a fluffy mixture;

[0111] S2 homogenization process: The mixture obtained by the primary mixing equipment is homogenized by a colloid mill. The temperature range of the mixture during the homogenization process is 40-45°C to obtain a uniform mixture;

[0112] S3 molding process: add the uniform mixture into a 227mm×160mm×30mm mold with a polytetrafluoro coating on the surface, and use the mold to press and mold under a hydraulic press. The feed weight is 1741.4g, the molding temperature is 45±5℃, and the molding pressure is 9.5MPa;

[0113] S3 curing process: Take out the pressed material and place it under 100mW / cm 2 The front and back sides were irradiated for 80 seconds under a metal halide lamp, and the irradiation dose for each side was 8J / cm 2 ; The starting temperature of the curing material is 30-35°C, and the highest temperature of the material after curing is 71°C;

[0114] S3 grinding process: In order to facilitate installation, the cured material can be grinded by CNC (numerical control machine) to obtain a composite thermal runaway protection material R-30 with a smooth surface. The highest temperature of the material during the grinding process is 46°C.

[0115] The UV curing encapsulation resin UV-4 and its preparation method are the same as those in Example 2.

[0116] The thermal conductivity, material enthalpy, density, average thickness and compressive strength of the composite thermal runaway protection material R-30 prepared in this embodiment are measured and are shown in Table 2.

[0117] Embodiment 4:

[0118] A rapid preparation method of a composite thermal runaway protection material, wherein the composite thermal runaway protection material comprises, by mass percentage, 87% magnesium chloride hexahydrate, 5% polyvinyl alcohol, 0.3% hexadecanedioic acid, and 7.7% UV-curable encapsulation resin UV-3. The preparation method is as follows:

[0119] S1 mixing process: 870g magnesium chloride hexahydrate, 50g polyvinyl alcohol, 3g hexadecanedioic acid, and 77g UV curing encapsulation resin UV-3 are added into a primary mixing kettle, and stirred while adding. The temperature range of the mixture during the mixing process is 20-30°C, and the mixing time is 15 minutes. Vacuum and remove bubbles to obtain a fluffy mixture;

[0120] S2 homogenization process: The mixture obtained by the primary mixing equipment is homogenized by a three-roller mill. The temperature of the mixture during the homogenization process ranges from 20 to 30°C to obtain a uniform mixture;

[0121] S3 molding process: add the uniform mixture into a 227mm×160mm×2mm mold with a polytetrafluoro coating on the surface, and use the mold to press and mold under a hydraulic press. The feed weight is 117.1g, the molding temperature is 35±5℃, and the molding pressure is 10.5MPa;

[0122] S3 curing process: Take out the pressed material and place it under 100mW / cm 2 Irradiation under metal halide lamp for 40 seconds, the irradiation dose is 4J / cm 2 ; The starting temperature of the curing material is 30-35°C, and the highest temperature of the material after curing is 62°C;

[0123] S3 grinding process: In order to facilitate installation, the cured material can be grinded by CNC (numerical control machine) to obtain a composite thermal runaway protection material S-2 with a smooth surface. The highest temperature of the material during the grinding process is 48°C.

[0124] The UV curing encapsulation resin UV-3 and its preparation method are the same as those in Example 1.

[0125] Example 4 is based on Example 1, and some components and their mass percentages are changed. The thermal conductivity, enthalpy value, density, average thickness and compressive strength of the composite thermal runaway protection material S-2 prepared in this example are measured and are shown in Table 2.

[0126] Embodiment 5:

[0127] A rapid preparation method of a composite thermal runaway protection material, wherein the composite thermal runaway protection material comprises, by mass percentage, 85% of potassium aluminum sulfate dodecahydrate, 2% of spherical silicon powder, 3% of polyvinyl alcohol, 0.3% of hexadecanedioic acid, and 9.7% of UV-curable encapsulation resin UV-4. The preparation method is as follows:

[0128] S1 mixing process: 850g of potassium aluminum sulfate dodecahydrate, 20g of spherical silicon powder, 30g of polyvinyl alcohol, 3g of hexadecanedioic acid, and 97g of UV curing encapsulation resin UV-4 are added into a primary mixing kettle, and stirred while adding. The temperature range of the mixture during the mixing process is 30-35°C, and the mixing time is 25 minutes. Vacuum and remove bubbles to obtain a fluffy mixture;

[0129] S2 homogenization process: The mixture obtained by the primary mixing equipment is homogenized by a calender. The temperature range of the mixture during the homogenization process is 40-45°C to obtain a uniform mixture;

[0130] S3 molding process: add the uniform mixture into a 227mm×160mm×10mm mold with a polytetrafluoro coating on the surface, and use the mold to press and mold under a hydraulic press. The feed weight is 585.4g, the molding temperature is 40±5℃, and the molding pressure is 9.5MPa;

[0131] S3 curing process: Take out the pressed material and place it under 100mW / cm 2 Irradiation under metal halide lamp for 60 seconds, the irradiation dose is 6J / cm 2 ; The starting temperature of the curing material is 30-35°C, and the maximum temperature of the material after curing is 70°C;

[0132] S3 grinding process: In order to facilitate installation, the cured material can be grinded by CNC (numerical control machine) to obtain a composite thermal runaway protection material S-10 with a smooth surface. The maximum temperature of the material during the grinding process is 45°C.

[0133] The UV curing encapsulation resin UV-4 and its preparation method are the same as those in Example 2.

[0134] Example 5 is based on Example 2, and some components and their mass percentages are changed. The thermal conductivity, enthalpy value, density, average thickness and compressive strength of the composite thermal runaway protection material S-10 prepared in this example are measured and are shown in Table 2.

[0135] Embodiment 6:

[0136] A rapid preparation method of a composite thermal runaway protection material, wherein the composite thermal runaway protection material comprises, by mass percentage: 26.4% potassium aluminum sulfate dodecahydrate, 60% magnesium chloride hexahydrate, 1% quartz chopped fiber, 1% silicon powder, 1% polyvinyl alcohol, 0.6% eicosanedioic acid, and 10% UV curing encapsulation resin UV-4. The preparation method is as follows:

[0137] S1 mixing process: 528g of potassium aluminum sulfate dodecahydrate, 1200g of magnesium chloride hexahydrate, 20g of quartz chopped fiber, 20g of silicon powder, 20g of polyvinyl alcohol, 12g of eicosanedioic acid, and 200g of UV curing encapsulation resin UV-4 are added into a primary mixing kettle, and stirred while adding. The temperature range of the mixture during the mixing process is 30-35°C, and the mixing time is 25 minutes. Vacuum the mixture to remove bubbles and obtain a fluffy mixture;

[0138] S2 homogenization process: The mixture obtained by the primary mixing equipment is homogenized by a colloid mill. The temperature range of the mixture during the homogenization process is 40-45°C to obtain a uniform mixture;

[0139] S3 molding process: add the uniform mixture into a 227mm×160mm×30mm mold with a polytetrafluoro coating on the surface, and use the mold to press and mold under a hydraulic press. The feed weight is 1762.2g, the molding temperature is 45±5℃, and the molding pressure is 10.2MPa;

[0140] S3 curing process: Take out the pressed material and place it under 100mW / cm 2 The front and back sides were irradiated for 80 seconds under a metal halide lamp, and the irradiation dose for each side was 8J / cm 2 ; The starting temperature of the curing material is 30-35°C, and the maximum temperature of the material after curing is 70°C;

[0141] S3 grinding process: In order to facilitate installation, the cured material can be grinded by CNC (numerical control machine) to obtain a composite thermal runaway protection material S-30 with a smooth surface. The highest temperature of the material during the grinding process is 48°C.

[0142] The UV curing encapsulation resin UV-4 and its preparation method are the same as those in Example 2.

[0143] Example 6 is based on Example 3, and some components and their mass percentages are changed. The thermal conductivity, enthalpy value, density, average thickness and compressive strength of the composite thermal runaway protection material S-30 prepared in this example are measured and shown in Table 2.

[0144] Comparative Example 1:

[0145] A rapid preparation method of a composite thermal runaway protection material, wherein the composite thermal runaway protection material comprises, by mass percentage, 40% hydrated silicate, 34.7% magnesium chloride hexahydrate, 5% polyvinyl alcohol, 0.3% hexadecanedioic acid, and 20% UV curing encapsulation resin UV-3. The preparation method, feeding mass and pressure, and radiation dose are the same as those in Example 1.

[0146] The UV curing encapsulation resin UV-3 and its preparation method are the same as those in Example 1.

[0147] Comparative Example 1 is based on Example 1, and the mass percentages of some components are changed, wherein the content of UV-curing encapsulation resin UV-3 exceeds the protection scope of the present invention. The thermal conductivity, enthalpy value, density, average thickness and compressive strength of the composite thermal runaway protection material D-A2 prepared in this comparative example are measured and are shown in Table 2.

[0148] Comparative Example 2:

[0149] A rapid preparation method of a composite thermal runaway protection material, wherein the composite thermal runaway protection material comprises, by mass percentage, 48% hydrated silicate, 45% magnesium chloride hexahydrate, 5% polyvinyl alcohol, 0.3% hexadecanedioic acid, and 1.7% UV curing encapsulation resin UV-3. The preparation method, feeding mass and pressure, and radiation dose are the same as those in Example 1.

[0150] The UV curing encapsulation resin UV-3 and its preparation method are the same as those in Example 1.

[0151] Comparative Example 2 is based on Example 1, but the mass percentages of some components are changed. The UV-3 content of the UV-curing encapsulation resin in Comparative Example 2 is too low, and it is found during the implementation that molding is impossible.

[0152] Comparative Example 3:

[0153] A rapid preparation method of a composite thermal runaway protection material, wherein the composite thermal runaway protection material comprises, by mass percentage, 40% hydrated silicate, 45% magnesium chloride hexahydrate, 5% polyvinyl alcohol, 0.3% hexadecanedioic acid, and 9.7% UV curing encapsulation resin UV-5. The preparation method, feeding mass and pressure, and radiation dose are the same as those in Example 1.

[0154] The UV curing encapsulation resin UV-5 comprises the following components by mass percentage: 69.4% of polyurethane acrylate Changxing 6148-J75, 1% of bisphenol A epoxy resin, 15% of epoxy acrylate, 1% of acrylic acid, 10% of active monomer (dipropylene glycol diacrylate), 0.5% of p-toluenesulfonyl isocyanate, 1% of photoinitiator (184), 1% of 4-acryloxybenzophenone, 1% of photoinitiator (TPO), and 0.1% of inhibitor (p-hydroxyanisole); the preparation method thereof is the same as that of the UV curing encapsulation resin UV-3 in Example 1.

[0155] Comparative Example 3 is based on Example 1, except that the UV-curable encapsulation resin UV-3 is replaced by the UV-curable encapsulation resin UV-5, and the siloxane-epoxy resin composite modified polyurethane acrylate Si / EP-PUA1 and the siloxane-polyurethane composite modified epoxy acrylate Si / PUA-EP1 in this example are not used. The thermal conductivity, enthalpy value, density, average thickness and compressive strength of the composite thermal runaway protection material D-C2 prepared in this comparative example are shown in Table 2.

[0156] Performance tests were performed on Examples 1 to 6 and Comparative Examples 1 to 3, and the results are shown in Table 2.

[0157] Table 2 Performance test of the embodiment

[0158]

[0159] Note: ① Thermal conductivity refers to ISO 22007-2 test;

[0160] ② Differential scanning calorimetry test;

[0161] ③ Density = weight / volume;

[0162] ④Compression strength refers to GB / T 1041-2008 test.

[0163] The enthalpy values ​​prepared in Comparative Example 1 are all smaller than those in Examples 1 to 6, and cannot meet the rapid heat absorption requirements of the battery thermal runaway process. The content of UV-curable encapsulation resin in Comparative Example 2 is too low, and the prepared thermal protection material cannot be formed. The UV-curable encapsulation resin in Comparative Example 3 does not use siloxane-epoxy resin composite modified polyurethane acrylate and siloxane-polyurethane composite modified epoxy acrylate, and the bonding force between the glue and the heat-absorbing material is poor, and the prepared material has low compressive strength.

[0164] Test example:

[0165] In order to test the thermal runaway effect of the composite thermal runaway protection material of the present invention, a test platform was built. Two soft-pack lithium iron phosphate batteries with an outer dimension of 227x160x7.25mm, a standard voltage of 3.3V, and a fully charged capacity of 20AH are numbered 1 and 2 respectively. The composite thermal runaway protection material prepared in the embodiment and the comparative example is sandwiched between battery No. 1 and battery No. 2, a heating plate with a power of 500W is attached to the right side of battery No. 1, and fixed with two upper and lower fixing fixtures, and the two batteries are connected to a signal acquisition device to collect the voltage of the two batteries and the temperature of the fitting surface of the two batteries and the composite thermal runaway protection material. A blank sample without the composite thermal runaway protection material and a sample of 2mm glass fiber aerogel are also made. Its structure is as follows Figure 4 shown.

[0166] The test steps are as follows: put the heating plate and the battery pack into an oven at 50±2℃, keep the temperature constant for 12 hours, power on the heating plate for heating, set the heating plate temperature power to 100%, and collect the battery voltage and temperature. When the voltage of battery No. 1 becomes 0V, stop heating, continue to collect the battery temperature, and stop collecting data until the temperature of both batteries drops below 50℃. The results are shown in Table 3.

[0167] Table 3 Application test of Examples 1 to 3 and Comparative Examples 1 to 3

[0168]

[0169]

[0170] Through the test, it is known that the blank sample without the composite thermal runaway protection material is completely thermally runaway when heated on the heating plate. The maximum temperature of the battery reaches 385°C, and the adjacent battery 2 also has thermal runaway. Due to the thermal insulation effect of the aerogel, the internal temperature of the No. 1 battery of the sample using aerogel rises faster, and the 196S is completely thermally runaway. The maximum temperature also reaches 475°C, which is 90°C higher than the blank sample, and the adjacent No. 2 battery also has thermal runaway.

[0171] In the test using the 2mm composite thermal runaway protection material R-2 of the present invention, the adjacent No. 2 battery did not have thermal runaway, and the time for the No. 1 battery voltage to drop to 0 was nearly twice as long as the blank sample. The maximum temperature of the battery during the entire test process was 272°C, which was more than 100°C lower than the blank sample temperature. After the test, the thermal conductivity of the composite thermal runaway protection material was 0.072W / (mK), which had a good heat insulation effect. The maximum temperature of the adjacent No. 2 battery was 119°C. This is lower than the thermal runaway temperature of lithium iron phosphate batteries reported in the literature of 150°C (Mei Wenxin, et al., Simulation Study on High-temperature Thermal Runaway of Large Lithium Iron Phosphate Batteries [J]. Energy Storage Science and Technology, 2021, 10(1): 202-209).

[0172] In the test using the 10mm composite thermal runaway protection material R-10 of the present invention, the adjacent battery No. 2 did not have thermal runaway, and the time for the voltage of battery No. 1 to drop to 0 was nearly twice as long as the blank sample. The maximum temperature of the battery during the entire test process was 257°C, which was more than 120°C lower than the temperature of the blank sample. The thermal conductivity of the composite thermal runaway protection material after the test was 0.218W / (mK), indicating that there was a surplus of material and it had not yet been completely decomposed. The maximum temperature of the adjacent battery No. 2 was 96°C. This is lower than the thermal runaway temperature of lithium iron phosphate batteries reported in the literature of 150°C (Mei Wenxin, et al. Simulation study on high-temperature thermal runaway of large lithium iron phosphate batteries [J]. Energy Storage Science and Technology, 2021, 10(1): 202-209).

[0173] In the test using the 30mm composite thermal runaway protection material R-30 of the present invention, the adjacent battery No. 2 did not have thermal runaway, and the time for the voltage of battery No. 1 to drop to 0 was nearly 1.5 times longer than that of the blank sample. The maximum temperature of the battery during the entire test process was 232°C, which was more than 120°C lower than the temperature of the blank sample. The thermal conductivity of the composite thermal runaway protection material after the test was 0.502W / (mK), indicating that there was a surplus of material and it had not yet been completely decomposed. The maximum temperature of the adjacent battery No. 2 was 74°C. This is lower than the thermal runaway temperature of lithium iron phosphate batteries reported in the literature of 150°C (Mei Wenxin, et al. Simulation study on high-temperature thermal runaway of large lithium iron phosphate batteries [J]. Energy Storage Science and Technology, 2021, 10(1): 202-209).

[0174] The 2mm composite thermal runaway protection materials of Comparative Examples 1 to 3 were used for testing. No material extrusion occurred in Comparative Example 1, but due to the low thermal enthalpy value of the material, the heat of Battery No. 1 could not be quickly absorbed, and the ratio was not optimized. The thermal conductivity of the material after decomposition reached 0.158W / (mK), and the thermal insulation effect was also poor, causing the adjacent Battery No. 2 to eventually thermally runaway. The thermal runaway protection material of Comparative Example 2 was not tested because it could not be formed. The thermal runaway protection material of Comparative Example 3 had a low compression strength, and the material was squeezed and cracked during the test, and then squeezed out, resulting in incomplete fitting of the material to the battery and a decrease in the amount of material. Although the time for the voltage of Battery No. 1 to drop to 0 was eventually extended, Battery No. 2 still experienced thermal runaway.

[0175] The above experiments fully demonstrate that the composite thermal runaway protection material prepared using the rapid prototyping process of the present invention has an obvious effect in preventing the spread of battery thermal runaway by first absorbing heat to quickly reduce the battery temperature and then insulating to prevent heat from being transferred to adjacent batteries.

[0176] The above are only specific application examples of the present invention and do not constitute any limitation on the protection scope of the present invention. In addition to the above embodiments, the present invention may also have other implementations. Any technical solution formed by equivalent replacement or equivalent transformation falls within the scope of protection claimed by the present invention.

Claims

1. A rapid preparation method of a composite thermal runaway protection material, characterized in that: The composite thermal runaway protection material includes the following components by mass percentage: 71-95% of inorganic heat absorbing material, 0-5% of inorganic light guiding material, 0-12% of polyvinyl alcohol, 0-1% of long-chain alkyl diacid and 5-16% of UV curing encapsulation resin; The rapid preparation method of the composite thermal runaway protection material is as follows: S1, using a mixing process to obtain a fluffy mixture; S2, through a homogenization process, the fluffy mixture is homogenized by a secondary homogenization device, the temperature of the mixture during the homogenization process is 0 to 80° C., and a uniform mixture is obtained; S3. Performing a molding process and a curing process on the uniform mixture to obtain a composite thermal runaway protection material.

2. The rapid preparation method of a composite thermal runaway protection material according to claim 1, characterized in that: In the step S1, the mixing process adds the inorganic heat absorbing material, the inorganic light guiding material, the polyvinyl alcohol, the long-chain alkyl diacid and the UV curing encapsulation resin into a primary mixing device, stirs while adding, the temperature range of the mixture during the mixing process is 0 to 80° C., the mixing time is greater than 10 minutes, and the air bubbles are removed by vacuum to obtain a fluffy mixture; The fluffy mixture has a specific gravity of less than 1g / cm 3 ; In the step S3, the molding process adds the uniform mixture into a mold and uses a press to press to obtain a molding material, the molding temperature is 0 to 80° C., and the molding pressure is greater than 3 MPa; In step S3, the curing process takes out the molding material and uses a UV lamp to cure it on one side or both sides. The curing starting material temperature is 0 to 60° C., and the highest temperature of the material after curing does not exceed 80° C.

3. The rapid preparation method of a composite thermal runaway protection material according to claim 1, characterized in that: The method also includes a grinding process, in which the material after the curing process in step S3 is ground to obtain a composite thermal runaway protection material with a flat and smooth surface, and the material temperature does not exceed 80° C. during the grinding process.

4. The rapid preparation method of a composite thermal runaway protection material according to claim 1, characterized in that: In the step S2, the secondary homogenization equipment includes any one of a three-roll mill, a calender, a sand mill, a roller press or a colloid mill.

5. The rapid preparation method of a composite thermal runaway protection material according to claim 1, characterized in that: The inorganic endothermic material includes any one or more of sodium acetate trihydrate, ammonium ferric oxalate trihydrate, magnesium sulfate heptahydrate, zinc sulfate heptahydrate, sodium carbonate decahydrate, calcium chloride hexahydrate, magnesium chloride hexahydrate, aluminum nitrate nonahydrate, ammonium pentaborate octahydrate, ammonium ferric sulfate dodecahydrate, ferrous chloride tetrahydrate, ammonium oxalate monohydrate, sodium tetraborate decahydrate, sodium tetraborate pentahydrate, aluminum sulfate 18hydrate, ammonium pentaborate, ammonium hydrogen borate tetrahydrate, boric acid, barium hydroxide octahydrate, pentahydrate and sodium silicate, hydrated sodium aluminum silicate, silicic acid, hydrated silicic acid, potassium aluminum sulfate dodecahydrate, sodium sulfate decahydrate, copper sulfate heptahydrate, ferrous sulfate heptahydrate, cobalt chloride hexahydrate or calcium sulfate dihydrate, in any proportion.

6. The rapid preparation method of a composite thermal runaway protection material according to claim 1, characterized in that: The inorganic light-guiding material is a material with ultraviolet light transmittance, including any one or more of spherical silicon powder, granular silicon powder, glass powder, quartz chopped fibers or a mixture of glass chopped fibers in any proportion.

7. The rapid preparation method of a composite thermal runaway protection material according to claim 1, characterized in that: The long-chain alkyl diacid includes a mixture of any one or more of dodecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid or eicosanedioic acid in any proportion; The polyvinyl alcohol is in powder form.

8. The rapid preparation method of a composite thermal runaway protection material according to claim 1, characterized in that: The composite thermal runaway protection material is cut into suitable sizes according to the structure of the battery pack and packaged in a sealed and pressure-resistant shell.

9. The rapid preparation method of a composite thermal runaway protection material according to claim 1, characterized in that: The composite thermal runaway protection material is used alone as a thermal runaway protection material, or is used in combination with a thermal insulation material or a physical thermal insulation structure to form a thermal protection system.

10. The rapid preparation method of a composite thermal runaway protection material according to claim 1, characterized in that: The UV curing encapsulation resin comprises, by mass percentage: 25-70% of siloxane-epoxy resin composite modified polyurethane acrylate, 10-30% of siloxane-polyurethane composite modified epoxy acrylate, 0-5% of epoxy resin, 5-40% of epoxy acrylate, 0-1% of acrylic acid, 5-30% of active monomer, 0-20% of silane modified resin, 0.1-3% of dehydrating agent, 0.1-3% of photoinitiator and 0.01-0.3% of polymerization inhibitor; The preparation method of UV curing encapsulation resin is as follows: add the siloxane-epoxy resin composite modified polyurethane acrylate, siloxane-polyurethane composite modified epoxy acrylate, epoxy resin, epoxy acrylate, acrylic acid, active monomer, silane modified resin, photoinitiator and inhibitor in the above components into a reactor according to a proportion, maintain stirring at 50-60° C. for 2-3 hours, add a dehydrating agent, stir for 10-30 minutes, and obtain a UV curing encapsulation resin.

11. The rapid preparation method of a composite thermal runaway protection material according to claim 10, characterized in that: The epoxy resin includes any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol E epoxy resin, bisphenol S epoxy resin, epoxy soybean oil, cardanol modified epoxy resin, trimethylolpropane triglycidyl ether, hexanediol diglycidyl ether or phenyl glycidyl ether in any proportion; The epoxy acrylate includes CN104 NS or CN120 NS of Sartomer; The active monomers include a mixture of any one or more of isobornyl acrylate, 2-cyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, 1,6-hexanediol diacrylate, isobornyl methacrylate or tetrahydrofurfuryl methacrylate in any proportion; The silane-modified resin is a mixture of any one or more of silane-modified polyether resin, silane-modified polyacrylate resin, silane-modified polyurethane resin, silane-modified polyester resin or alkoxy silicone resin in any proportion; The dewatering agent is p-toluenesulfonyl isocyanate; The photoinitiator includes any one or more of 4-benzoyl-4'-methyl-diphenyl sulfide, 2,4,6-trimethylbenzoyldiphenyl phosphine oxide, 2,4,6-trimethylbenzoylphosphonic acid ethyl ester, bis(2,4,6-trimethylbenzyl acyl)phenyl phosphine oxide, benzoin dimethyl ether, 2-methyl-1-(4-methylmercaptophenyl)-2-morpholine-1-propanone, 1-hydroxycyclohexyl benzophenone, 4-acryloyloxybenzophenone or methyl o-benzoylbenzoate, and the mixture is in any proportion.

12. The rapid preparation method of a composite thermal runaway protection material according to claim 10, characterized in that: The preparation method of the siloxane-epoxy resin composite modified polyurethane acrylate is as follows: A1, adding diisocyanate and hydroxy acrylate in a molar ratio of 1:1 into reactor A, adding 0.01-0.2% of the total mass of diisocyanate and hydroxy acrylate as catalyst dibutyltin dilaurate, and 0.01-0.2% of the total mass of diisocyanate and hydroxy acrylate as inhibitor p-hydroxyanisole, raising the temperature to 40-60° C. for reaction for 1-3 hours to obtain a semi-adduct of diisocyanate and hydroxyethyl acrylate, and calculating the theoretical NCO equivalent; A2, adding epoxy resin and mercaptosilane coupling agent into reactor B in a molar ratio of epoxy bond to mercapto group of 1:1, adding catalyst triethylamine in an amount of 0.01-0.2% of the total mass of epoxy resin and mercaptosilane coupling agent, heating to 70-90° C. for reaction for 1-3 hours to obtain siloxane-modified epoxy resin, and calculating the theoretical hydroxyl equivalent; A3. According to the calculation method of NCO equivalent: hydroxyl equivalent = semi-adduct mass: siloxane-modified epoxy resin mass, a set amount of siloxane-modified epoxy resin is added into reactor A, 0.01-0.2% of the total mass of the siloxane-modified epoxy resin as a catalyst dibutyltin dilaurate and 0.01-0.2% of the total mass of the siloxane-modified epoxy resin as an inhibitor p-hydroxyanisole are added, and the reaction is stirred at 60-80° C. for 2-8 hours until the isocyanate absorption peak disappears, thereby obtaining the siloxane-epoxy resin composite modified polyurethane acrylate.

13. The rapid preparation method of a composite thermal runaway protection material according to claim 12, characterized in that: In step A1, 0 to 30% of the total mass of diisocyanate and hydroxy acrylate and 1 to 6 functional acrylate monomers without hydroxyl structure are added; in step A2, 0 to 30% of the total mass of epoxy resin and mercaptosilane coupling agent and 1 to 6 functional acrylate monomers without hydroxyl structure are added; or In step A1, 0 to 30% of the total mass of diisocyanate and hydroxy acrylate and 1 to 6 functional acrylate monomers without hydroxyl structure are added; in step A3, 0 to 30% of the total mass of siloxane-modified epoxy resin and 1 to 6 functional acrylate monomers without hydroxyl structure are added; or In step A2, 0 to 30% of the total mass of epoxy resin and mercaptosilane coupling agent is added to a 1-6-functional acrylate monomer that does not contain a hydroxyl structure; in step A3, 0 to 30% of the total mass of siloxane-modified epoxy resin is added to a 1-6-functional acrylate monomer that does not contain a hydroxyl structure; or In step A1, 0 to 30% of the total mass of diisocyanate and hydroxyl acrylate and 1 to 6 functional acrylate monomers without hydroxyl structure are added; in step A2, 0 to 30% of the total mass of epoxy resin and mercaptosilane coupling agent and 1 to 6 functional acrylate monomers without hydroxyl structure are added; in step A3, 0 to 30% of the total mass of siloxane-modified epoxy resin and 1 to 6 functional acrylate monomers without hydroxyl structure are added.

14. The rapid preparation method of a composite thermal runaway protection material according to claim 12, characterized in that: In step A1, 0 to 30% of the total weight of diisocyanate and hydroxy acrylate and a 1-6 functional acrylate monomer without a hydroxyl structure is added; or In step A2, 0 to 30% of the total weight of the epoxy resin and the mercaptosilane coupling agent is added to a 1-6-functional acrylate monomer that does not contain a hydroxyl structure; or In step A3, 0 to 30% of the total mass of the siloxane-modified epoxy resin is added with 1-6 functional acrylate monomers that do not contain a hydroxyl structure.

15. The rapid preparation method of a composite thermal runaway protection material according to claim 12, characterized in that: The hydroxy acrylate includes any one or more of 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-hydroxypropyl acrylate, 2-hydroxybutyl acrylate or 4-hydroxybutyl acrylate in any proportion; The epoxy resin includes any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol E epoxy resin, bisphenol S epoxy resin, epoxidized soybean oil, cardanol modified epoxy resin, trimethylolpropane triglycidyl ether, hexanediol diglycidyl ether or phenyl glycidyl ether in any proportion.

16. The rapid preparation method of a composite thermal runaway protection material according to claim 10, characterized in that: The preparation method of the siloxane-polyurethane composite modified epoxy acrylate is as follows: B1, adding diisocyanate and mercaptosilane coupling agent in a molar ratio of 1:1 into reactor C, adding 0.01-0.2% of the total mass of diisocyanate and mercaptosilane coupling agent as catalyst dibutyltin dilaurate, heating to 70-100° C. and reacting for 4-8 hours to obtain a semi-adduct of diisocyanate and mercaptosilane coupling agent; B2. Add a set mass of epoxy acrylate to the reactor C at a molar ratio of diisocyanate to epoxy acrylate of 1:1 to 1:0.5, add a catalyst dibutyltin dilaurate of 0.01 to 0.2% of the total mass of epoxy acrylate, maintain the temperature at 70 to 90° C. for 1 to 3 hours to obtain siloxane-polyurethane composite modified epoxy acrylate.

17. A rapid preparation method of a composite thermal runaway protection material according to claim 16, characterized in that: In step B1, 0 to 30% of the total mass of diisocyanate and mercaptosilane coupling agent is added with 1-6 functional acrylate monomers without hydroxyl structure; in step B2, 0 to 30% of the total mass of epoxy acrylate is added with 1-6 functional acrylate monomers without hydroxyl structure.

18. The rapid preparation method of a composite thermal runaway protection material according to claim 16, characterized in that: In step B1, 0 to 30% of the total weight of diisocyanate and mercaptosilane coupling agent in an acrylate monomer having 1 to 6 functions and not containing a hydroxyl structure is added; Or in step B2, 0 to 30% of the total mass of epoxy acrylate is added with 1-6 functional acrylate monomers that do not contain hydroxyl structures.

19. The rapid preparation method of a composite thermal runaway protection material according to any one of claims 12 to 18, characterized in that: The diisocyanate includes any one or more of hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, xylylene diisocyanate, trimethylhexane diisocyanate, 1,5-naphthalene diisocyanate or diphenylmethane diisocyanate in any proportion; The mercaptosilane coupling agent includes any one or more of mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane, mercaptopropylmethyldimethoxysilane or mercaptopropylmethyldiethoxysilane in any proportion.

20. The method for rapidly preparing a composite thermal runaway protection material according to any one of claims 13, 14, 17 or 18, characterized in that: The acrylate monomer includes a mixture of any one or more of isobornyl acrylate, 2-cyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, 1,6-hexanediol diacrylate, isobornyl methacrylate or tetrahydrofurfuryl methacrylate in any proportion.

Citation Information

Patent Citations

  • A rapidly heat-absorbing thermal runaway protection material and its preparation method

    CN116423939B